2014
DOI: 10.1128/aac.02522-14
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antiretroviral Therapy in Rhesus Macaques Improves RT-SHIV Viral Decay Kinetics

Abstract: spectrometry (LC-MS-MS). Viral loads were monitored with a standard TaqMan quantitative reverse transcriptase PCR (qRT-PCR) assay. Comprehensive analyses of replication dynamics were performed. RT-SHIV infection in rhesus macaques produced typical viral infection kinetics, with untreated controls establishing persistent viral loads of >104 copies of RNA/ml. RT-SHIV loads at the start of treatment (V 0 ) were similar in all treated cohorts (P > 0.5). All antiretroviral drug levels were measureable in plasma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Nevertheless, all four animal studies also showed that the dominant antiviral effect of the antibodies tested was virus neutralization that prevented new rounds of infection. We are able to reach these quantitative conclusions because prior studies of HIV-1 dynamics in infected humanized mice ( 18 , 45 ) and SIV or SHIV dynamics on infected rhesus macaques ( 46 48 ) have been found to be similar to that reported for HIV-1 dynamics in patients.…”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, all four animal studies also showed that the dominant antiviral effect of the antibodies tested was virus neutralization that prevented new rounds of infection. We are able to reach these quantitative conclusions because prior studies of HIV-1 dynamics in infected humanized mice ( 18 , 45 ) and SIV or SHIV dynamics on infected rhesus macaques ( 46 48 ) have been found to be similar to that reported for HIV-1 dynamics in patients.…”
Section: Discussionsupporting
confidence: 62%
“…However, non-human primate models used to evaluate anti-HIV-1 RT inhibitor efficacy often employ SIV encoding HIV-1 RT in lieu of SIV RT; HIV-1 RT is substituted in place of SIV RT given the differences between these enzymes and NNRTI efficacy (Ambrose et al, 2004, 2014; Balzarini et al, 1995; North et al, 2014; Wang et al, 2014; Witvrouw et al, 2004). Although the importance of substituting HIV-1 RT in lieu of SIV RT in this context is recognized, the relationship between Vpx and evaluation of NRTI efficacy in the context of RT-SHIV constructs, to our knowledge, has not been addressed prior to this report.…”
Section: Discussionmentioning
confidence: 99%
“…It was highly expected that these SHIVs are very useful to study the basic virus property in vivo, the effect of antiviral drugs in vivo, the emergence of drug-resistance variants, and/or the host immunological responses associated with the concerned viral proteins. In fact, a large number of scientific reports on SHIV-RTs have been published (for example, see references [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]). More impressively, SHIV-Env constructs have played a critical role in the HIV-1/AIDS research activity as fully revealed by selected, only a small portion of scientific articles published so far .…”
Section: Siv/shiv Clones and Nonhuman Primate Modelsmentioning
confidence: 99%